General Self-Efficacy and Health Literacy Levels of Students Parents: Investigation in Two Primary Schools in Ankara (Turkey Health Literacy Journal, 2020)
Parents’ health literacy level is an important factor in health prevention and promotion as well as for community health. Objectives:This study aimed to examine the relationship between general selfefficacy and health literacy levels. Method: This cross-sectional study was conducted between May and June 2016 in two primary schools located in two districts of Ankara. The sample was selected among parents of students attending 1st- 4th years of primary school. Descriptive questions, Turkey Health Literacy and general self-efficacy scales were included in the survey and 226 parents were evaluated. Pearson Chi-square, Fisher’s Exact, Kolmogorov-Smirnov, Mann-Whitney U, Student’st, Kruskal- Wallis one-way analysis of variance and Spearman correlation tests were used for the analysis. Results: 64.6% of participants had inadequate-limited health literacy and general selfefficacy score was 62.63(±10.34). A positive, powerful and statistically significant relationship was found between general self-efficacy and health literacy(r=0,70,p<0,05). A statistically significant relationship was found between health literacy and general self-efficacy levels and educational level of participants (p<0,001). Conclusion: On the basis of this study, we can say that there is a powerful relationship between health literacy and general self efficacy. Efforts to promote health literacy will allow the improvement of self-efficacy, which is also an important determinant in the initiation and maintenance of health promoting behaviours.